Capacitance Control on the Wire Production Line; MATEC Web of Conferences; Vol. 79 : Information-Measuring Equipment and Technologies (IME&T 2016) - Goldstein (Goldshtein) A. E. Aleksandr Efremovich (2016, 2016)
Title screen